If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 6x = 9 + -1x Combine like terms: x + 6x = 7x 7x = 9 + -1x Solving 7x = 9 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 7x + x = 9 + -1x + x Combine like terms: 7x + x = 8x 8x = 9 + -1x + x Combine like terms: -1x + x = 0 8x = 9 + 0 8x = 9 Divide each side by '8'. x = 1.125 Simplifying x = 1.125
| 7*3-2= | | 29.5u+548=2023 | | 2(4+y)-3y=9 | | 4.5/3=x/6.5 | | x/-6-21=-28 | | 16d-7=63 | | 5(15+3X)=375 | | -4(2-a)+3a=3(a-4) | | -12x-4=-5x-67 | | -82=6y-11y-17 | | 3(3-X)=54 | | 12+4x=2(12+4x) | | 10-8-5+2-7= | | 15(x-2)=240 | | 3p+3=2p+5 | | -8-a=-3(2a-4) | | ln(60/x) | | x^2y^9/2x^3y^6 | | 19x+12=11x-20 | | 5(x-3)=225 | | -11x-1=-15x-9 | | (5x^2+6x+4)-(3x^2-2x+8)= | | -8x+7=-12x+15 | | 2(x+4)=440 | | -15=18+0.75m | | 5=4x^2-6x+2 | | -2.8(x-2)-5.7(x-2.2)=-37.11 | | 25x+75=225 | | -14x-4=-13x+16 | | x+(3x-12)=180 | | g(5)=4x^2-6x+2 | | 2(2-x)=-3x-2forx |